Electroacupuncture Treatment for Obstructive Sleep Apnea Syndrome - Pan, Hong-hong; Jin, Ze; Wang, Yu-lin (Journal of acupuncture and tuina science, 2013)
Obsirucfive sleep atmea syndrome （OSAS） means that patients sutter tiom repetitive pauses in breathing, even hypoxemia and hypercapnia because ot upper aim,ay obstruction during sleep. The clinical symptoins are known as snoring, awakening from ditticulty, breathing, dayfinle sleepiness, morning headaches, memory loss, hypertension, pulmonary, hypertension, puhnonary heart disease, and severe symptoms like arrhythmia and even sudden death in sleep. Theretore, the OSAS causes widespread concern among the patients and the medical workers.